Peningkatan Kemampuan Menulis Puisi Pada Siswa Kelas VIII-1 MTS Negeri 2 Bungo Melalui Model Pembelajaran Menulis Terbimbing Strategi Inventaris Diksi - Zulyadaini Zulyadaini (Pusdikra Publishing, 2022)
This study aims to look at the Ability to Write Poetry in Class VIII-1 Students of MTS Negeri 2 Bungo Through the Guided Writing Learning Model Diction Inventory Strategy. The method used is class action research with a cycle model design, namely the stages of (1) planning, (2) implementation, (3) observation, and (4) reflection. As for the research results obtained by learning using the guided writing learning model the diction inventory strategy can improve learning outcomes. In the first cycle the level of student learning completeness reached 62.85% with good learning abilities. Meanwhile in cycle II the level of student learning completeness reached 82.85% with a very good level of learning ability.